2020
DOI: 10.3791/60641
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Traditional Fear Tests to Evaluate Different Emotional Circuits in Cattle

Abstract: Animal temperament is complex and has implications for productivity and economic profitability. Quantifying an animal's response to differing stimuli may facilitate breeding selections and identify animals that are better suited to specific management strategies. Multiple tests have been developed to evaluate cattle temperament (e.g., exit velocity, chute score, pen score, open field test, startle test, bovine zero maze), but each of these tests evaluates the animal's response to different stimuli (e.g., isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…In fighting bulls, human contact with animals is limited, sometimes until the bull enters the plaza, to preserve the fearfulness and aggressiveness towards people. The above agrees with Daigle et al [36], who mentions that temperament and human-animal interaction influence the perception and adaptation to various psychological stressors. It has been reported that the reactions derived from fear preserve the integrity of the animal and improve animal fitness.…”
Section: Stressors Of Psychological Originsupporting
confidence: 92%
“…In fighting bulls, human contact with animals is limited, sometimes until the bull enters the plaza, to preserve the fearfulness and aggressiveness towards people. The above agrees with Daigle et al [36], who mentions that temperament and human-animal interaction influence the perception and adaptation to various psychological stressors. It has been reported that the reactions derived from fear preserve the integrity of the animal and improve animal fitness.…”
Section: Stressors Of Psychological Originsupporting
confidence: 92%
“…Fear tests should be performed when the animals are still young, in order to minimize the influence coming from previous experiences. The results of these tests can not only give us information about the temperament of the animal, but may also give indications about the future productivity of the tested animal [ 14 ]. Both the novelty test and the human approach test are often used in animal fear studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle temperament is important for the cattle industry since it is related to productive and reproductive performance, work safety, and animal welfare [ 2 , 3 ]. There has also been a trend towards the genetic selection of docile and safe-to-handle animals, which has further promoted research on cattle temperament, mostly based on the observation of specific parameters with different levels of participation by observers and the incorporation of precision measuring devices [ 6 , 7 , 8 , 9 ]. Widespread attention has been given to the relationship between cattle temperament and the response to specific (human) handling practices, heritability, and some productive parameters [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%